PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA KELAS V DALAM PEMBELAJARAN IPAS DI SD - Rahmawati, Irda; Hanifah, Nurdinah; Aeni, Ani Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the Discovery Learning model on fifth-grade students’ learning outcomes in IPAS, focusing on the topic Local Economic Conditions. A quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design was applied. The sample included 60 students: 30 in the experimental group (Discovery Learning) and 30 in the control group (conventional learning). Data were collected through pretest and posttest. The results showed that the experimental group’s mean score increased from 66.46 to 86.76, while the control group increased from 55.26 to 69.66. Hypothesis testing indicated a significant difference between both groups (sig. 0.001 < 0.05). The N-Gain score was 0.62 (moderate) for the experimental group and 0.31 (low) for the control group. In conclusion, Discovery Learning is more effective in improving students’ IPAS learning outcomes than conventional instruction.